Antero de Alda e Alyssa Monks : a liquidez social nas poéticas contemporâneas - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The advent of new technologies of information and communication brought changes to human experiences in various fields. Social, political, economic, artistic and cultural have changed and continue to change at a rapid and increasing rate. This paper discusses, in this context, the aesthetic and formal aspects of cyberliterature and contemporary painting, with regard to the stage of social liquidity of contemporaneity. Search, therefore, answer the following question: How contemporary poetic account and are influenced by changes in liquid modernity? To that end, the research aims to: investigate the cyberculture and contemporary artistic production as an emerging element of a liquefied and accelerated society; relate the recurring themes in painting Alyssa Monks and ciberpoesia of Antero de Alda considering its works in a critical sociological perspective; discuss the thematic and aesthetic aspects of these works, regarding social fluidity that is presented in the art. For their theoretical, research is developed through a qualitative approach of the selected corpus, in the light of interdisciplinary theoretical framework in the areas of aesthetics, sociology. The results show that the modern artist is one who knows what's on shaky spell of his work, constituting therefore puzzles that can be solved, since it does not respond to alone. Thus, the spectator will seek the answers through new puzzles not only in the artist's personality, but on a path readings accusing the saturation of the uses of language.
Keywords: Poética contemporânea; Arte; Estética; Liquidez social; Contemporary poetics; Art; Aesthetics; Social liquidity; LETRAS::TEORIA LITERARIA; LETRAS::LITERATURAS CLASSICAS